Clinical, radiological, surgical, and pathological determinants of olfactory groove schwannoma - Andi Sadayandi Ramesh; Jagath Lal Gangadharan; Anita Mahadevan; Aravinda Hanumanthapura Ramalingaiah; Bhagavatula Indira Devi (Indian Journal of Neurosurgery)
Background Olfactory groove schwannomas (OGS) are rare anterior cranial fossa base tumors with only 41 cases reported in literature. Olfactory ensheathing cell schwannoma (OECS) has similar clinico-radiological features as OGS, but a different cell of origin. In recent years, there is growing interest in OECS as more cases are being reported.